Price Analysis, Marketing Communication, and Brand on Costumer Loyalty - Cyndy Melliani Pratiwi; Purnama Yanti Purba; James Han's; Stevent Tanadi (International Journal of Social Science and Business, 2021)
This study aims to test and analyze the influence of the test and analyze the influence of Price, Marketing Communication and Brand Loyalty of the Customers. The phenomenon of decrease in number of subscribers, the price of which is not optimal, marketing communication has not been satisfactory and brands that are less well interesting background of this research. The research method is quantitative approach, type of research is descriptive and quantitative nature of this research is descriptive explanatory. The population was 144 customers from January to December 2019. The sample in this study was 106 customers. The sampling technique used is simple random sampling. Testing the validity and reliability of 30 consumers taken from the rest of the population that is not used in the sample. The data was collected using questionnaires distributed to consumers as respondents, interviews were conducted with consumers, and documentation studies. Methods of data analysis is multiple linear regression analysis. The test results obtained the calculated F value (25.019) > F table (2.69) and the significance probability was 0.000 <0.05. The results of the calculation of partial hypothesis testing obtained tcount > ttable or 2,581 > 1,983 and significant obtained 0.011 < 0.05. So, it can be concluded that price analysis, marketing and brand communication has positive and significant effect on customer loyalty.